In praise of community: The case for consensus seeking within online networks - Hammond, Michael (Proceedings of the International Conference on Networked Learning, 2016)
This paper considers the idea of community in networked learning. Community is a contested concept both in terms of definition and in the ways in which we perceive the consequences of belonging to communities. While community is generally valued this has not always been the case. One particularly compelling example of a critique of online community was offered by Hodgson & Reynolds (2005). This critique was underpinned by three key arguments: we read technology naively; community is uncritically ‘privileged’; we overstate the importance of consensus. These three propositions are analysed in detail. First, there is considerable support for the idea that we have an overly determinist view of technology with, for example, some literature routinely shifting from statements as to what technology can do to statements as to how technology is likely to be used. This is naïve as in practice technology use is likely to be differentiated and shaped by wider social cultural factors. Second, while there is some support for the idea that community is privileged, there is always a balance to be made between the opportunities provided by community (for example enabling a social life and building a social identity) with the constraints of community (for example, a bias towards conformity and suppression of counter cultural thinking). Third, there is, again, support for the idea that consensus can be forced and that it may be more desirable for learners to explore positions in counter-cultural sub groups, or to strike looser forms of association, rather than experience the tensions and restrictions of community membership. However, the paper resists the conclusion that the search for community and consensus in itself is misplaced. Instead it is suggested we should not give up on a big idea about learning – that is learning involves the public airing of difference and reaching an accommodation with others by the force of the stronger argument. It is argued the search for consensus within what we might recognise as an ideal speech community remains a valuable educational aim.